2020
DOI: 10.4103/jcd.jcd_572_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of bond strength and microleakage of newer generation bonding agents to enamel and dentin: An in vitro study

Abstract: Aims: This study aims to evaluate the bond strength (BS) and microleakage (ML) of the newer bonding agents to enamel and dentin. Objective: (1) To analyze the BS between self-etch and total-etch adhesives. (2) To analyze the depth of ML between self-etch and total-etch adhesives. Materials and Methods: Sixty mandibular premolars were fabricated and randomly divided into three groups: Group I ( n = 20)-bonded with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…It is crucial to acknowledge the role of metal ions, such as, silver, copper, and zinc, which exhibit antimicrobial effects against diverse oral bacteria [33]. These ions disrupt bacterial cell membranes, inhibit enzyme activity, and interfere with bacterial metabolism, ultimately diminishing bacterial viability and suppressing VSC production [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to acknowledge the role of metal ions, such as, silver, copper, and zinc, which exhibit antimicrobial effects against diverse oral bacteria [33]. These ions disrupt bacterial cell membranes, inhibit enzyme activity, and interfere with bacterial metabolism, ultimately diminishing bacterial viability and suppressing VSC production [34].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study showed Adper Single Bond 2 in etch-and-rinse mode exhibited the highest shear bond strength to tooth dentin, irrespective of whether with or without diode laser irradiation prior to photopolymerization, compared to the use of Tetric N-Bond Universal, Prime, and Bond Universal self-etch adhesives. Hegde et al [ 14 ] study attributed having a separate step of acid etching of tooth dentin using 37% phosphoric acid (etch-and-rinse mode) to deeper penetration of subsequently placed dental adhesive into exposed collagen fibril scaffold with the formation of thicker, longer resin tags compared to self-etch adhesives with shorter resin tag formation, residual acidity, and hydrolytic instability, resulting in poor SBS to tooth dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Glass ionomer cements (GIC), which are routinely used as tooth-colored restorative materials. GICs can be considered as the first-choice materials, especially in the restorations of patients with high cariogenic activity, due to their fluoride release feature that gives them a cariostatic property (4,5). In addition, current restorative materials are being developed by combining the strength and esthetics of composites with the benefits of glass ionomers.…”
Section: Introductionmentioning
confidence: 99%